Analysis of the Risk of Market Competition in the Month of Ramadan in Improving the Economy of Takjil Traders in the Jati Utomo Village, North Binjai - Raihani Fadila; Mutiah Khaira Sihotang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The high activity of food trading for breaking the fast of takjil during the month of Ramadan in Jati Utomo Village, North Binjai raises the phenomenon of significant market competition, between permanent traders and seasonal traders. This competition creates risks for traders, especially in maintaining customers and income. This research formulates two main problems, namely what are the risks faced by takjil traders due to market competition, and how competition affects the economic improvement of traders. This study aims to analyze the form of market risk and its impact on the economic conditions of takjil traders during the month of Ramadan. The method used in this research is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation of five traders. The results of this study show that 60% of traders experienced an increase in income because they were able to innovate and adjust products to market tastes despite being faced with high market competition. Meanwhile, the other 40% experienced income stagnation due to lack of product innovation and lack of understanding of accurate financial records. This study concludes that the success of micro businesses in facing competition is not only influenced by marketing strategies, but also by the ability to innovate and financial literacy.